The Clinical Course of Bowel Urgency Severity Among Patients with Inflammatory Bowel Disease-A Real-World Study - James D. Lewis; Theresa Hunter Gibble; Mingyang Shan; Xian Zhou; April N. Naegeli; Ghadeer K. Dawwas (Adis, Springer Healthcare, 2024)
Abstract Background Bowel urgency is a highly burdensome symptom among patients with inflammatory bowel disease (IBD). Objectives To assess changes in severity of bowel urgency and identify predictors of worsening or improvement among patients with Crohn's disease (CD) and ulcerative colitis (UC) at 6 months from their enrollment visit. Methods Data from patients in the Study of a Prospective Adult Research Cohort with IBD were analyzed. Enrolled patients with CD or UC with 6-month visits were included. Changes and predictors of bowel urgency severity over 6 months in patients with CD or UC were examined using two separate analyses: (a) "worsening" versus "no change" excluding those with moderate-to-severe bowel urgency at enrollment, and (b) "improvement" versus "no change" excluding those with no bowel urgency at enrollment. The enrollment characteristics were compared within these groups. Results At baseline, in both CD and UC, use of biologics and/or immunomodulators at enrollment was similar across cohorts. Among patients with CD, 206 of 582 (35.4%) reported worsening, and 195 of 457 (42.7%) reported improvement in bowel urgency. Younger age (P = 0.013) and moderate-to-severe bowel urgency (P < 0.001) were associated with improvement. Moderate bowel urgency (P = 0.026) and bowel incontinence while awake (P = 0.022) were associated with worsening. Among patients with UC, 84 of 294 (28.6%) reported worsening, and 111 of 219 (50.7%) reported improvement in bowel urgency. Higher symptomatic disease severity (P = 0.011) and more severe bowel urgency (P < 0.001) were associated with improvement. Conclusions Bowel urgency is an unpredictable and unstable symptom among patients with IBD. Over 50% of patients with CD or UC experienced either worsening or improvement at 6 months postenrollment.